2015
DOI: 10.1007/s10802-015-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Sequence of Social Anxiety and Depressive Symptoms Following Interpersonal Stressors During Adolescence

Abstract: Social anxiety and depressive symptoms dramatically increase and frequently co-occur during adolescence. Although research indicates that general interpersonal stressors, peer victimization, and familial emotional maltreatment predict symptoms of social anxiety and depression, it remains unclear how these stressors contribute to the sequential development of these internalizing symptoms. Thus, the present study examined the sequential development of social anxiety and depressive symptoms following the occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 76 publications
6
65
0
1
Order By: Relevance
“…Social-cognitive processes might be less salient than emotional processes and might be less relevant in explaining why peer victimization affects adjustment and wellbeing. The summary of the reviewed studies suggests that explanations might generally be quite complex because chain mediations are likely where, for instance, peer victimization increases loneliness (Baker and Bugay 2011), which results in more depressive symptoms, which, in turn, predict higher anxiety (Hamilton et al 2016). Future studies are needed that elucidate the sequence of consequences of peer victimization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social-cognitive processes might be less salient than emotional processes and might be less relevant in explaining why peer victimization affects adjustment and wellbeing. The summary of the reviewed studies suggests that explanations might generally be quite complex because chain mediations are likely where, for instance, peer victimization increases loneliness (Baker and Bugay 2011), which results in more depressive symptoms, which, in turn, predict higher anxiety (Hamilton et al 2016). Future studies are needed that elucidate the sequence of consequences of peer victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Hamilton et al (2016) explored depression as mediator between peer victimization and anxiety and, vice versa, anxiety as mediator on the link between peer victimization and depression. Only the latter was empirically supported, that is, victimized adolescents were at greater risk for depression, which, in turn, increased their social anxiety risk.…”
Section: Mediators On Associations Between Peer Victimization and Intmentioning
confidence: 99%
“…It is important that depression and anxiety in particular are studied in adolescence (La Greca & Harrison, 2005). Social anxiety and depression are the two most widely en-countered psychological disorders (Davidson, Wingate, Grant, Judah & Mills, 2011), very often accompanying each other, as common mental health problems among adolescents (Hamilton et al, 2016;Klemanski, Curtiss, McLaughlin & Nolen-Hoeksema, 2016;La Greca, Ehrenreich-May, Mufson & Chan, 2016). High levels of social anxiety are common between the ages of 10 and 19.…”
Section: Introductionmentioning
confidence: 99%
“…Ollendick & Yule (1990) found that children with high levels of depression had high levels of social evaluation fear and anxiety, as well. Many studies showed that social anxiety accompanied depression and it was one of the important predictors of depression (Beesdo et al, 2007;Davidson et al, 2011;Gültekin & Dereboy, 2011;Horn & Wuyek, 2010;Ottenbreit, Dobson & Quigley, 2014;Stein et al, 2001;Hamilton et al, 2016;Kessler et al, 1999;Kocabaşoğlu, Doksat & Doğangün, 2004;Mehtalia & Vankar, 2004;Nepon, Flett, Hewitt & Molnar, 2011;Ohayon & Schatzberg, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Van Zalk and Tilfors () observed an association between social anxiety symptoms and prospective depressive symptoms in adolescents aged between 13 and 15‐year old but did not find evidence for an association in the reverse direction. In contrast, the opposite was observed in a study by Hamilton et al (), in which depressive symptoms were shown to be a precursor of social anxiety symptoms but social anxiety symptoms were not predictive of subsequent depressive symptoms following stress in a sample of adolescents between the ages of 12 and 13 years. The current study aims to further investigate the reciprocal associations between social anxiety symptoms and depressive symptoms throughout the entire period of adolescence.…”
Section: Introductionmentioning
confidence: 63%